Control of natural convection via inclined plate of CNT-water nanofluid in an open sided cubical enclosure under magnetic field. (August 2017) - Kolsi, Lioua; Alrashed, Abdullah A.A.A.; Al-Salem, Khaled; Oztop, Hakan F.; Borjini, Mohamed Naceur
Highlights: Computational analysis is studied for 3D MHD natural convection in an open cubical enclosure filled with CNT-water nanofluid. The cavity is heated from left vertical wall and an inclined plate is attached inside the cavity. The maximum heat transfer is formed when θ = 180°. Inclined plate is a passive control element for heat transfer to save energy. Abstract: A computational analysis has been performed in this work to solve three-dimensional magnetohydrodynamic natural convection in an open cubical enclosure filled with CNT-water nanofluid. The cavity is heated from left vertical wall and an inclined plate is attached inside the cavity with finite length. The study is solved for different governing parameters as Rayleigh number (10 3  ≤  Ra  ≤ 10 5 ), nanoparticle volume fraction (0% ≤ φ ≤ 5%), Hartmann number (0 ≤  Ha  ≤ 100) and inclination angle of the fin (0° ≤ θ ≤ 360°). It is observed that all of these parameters can be used as passive control element for heat and fluid flow and the maximum heat transfer is formed when θ = 180° but minimal value of average Nusselt number is changed according to nanoparticle addition into base fluid.